Tajdid Nikah: Legal Analysis, Ulama Perspectives, and Maslahah Mursalah (A Case Study in East Lampung Regency) - Nur Isti Fadah; Hud Leo Perkasa Maki; Hendra Irawan; Nency Dela Oktora; Husain Fadhil Arrasyid (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2025)
This study examines the phenomenon of tajdid nikah (renewal of the marriage contract) among Muslim couples in Giriklopomulyo Village, Sekampung District, East Lampung Regency, with a focus on cases involving pregnancy prior to the official marriage. Although both Islamic law and the Compilation of Islamic Law (KHI) Article 53 confirm that such marriages are valid without requiring re-contracting, tajdid nikah remains prevalent due to societal pressure, cultural norms, and insufficient legal literacy. Using a qualitative case study approach with data from interviews, documentation, and field observations, this research systematically analyzes five key dimensions: the definition of tajdid nikah, local chronology of its practice, its legal interpretation under KHI, contemporary ulama perspectives, and its relevance within the framework of maslahah mursalah. The findings show that tajdid nikah is often pursued not for legal necessity but to achieve psychological relief, family acceptance, and perceived social legitimacy. While some scholars tolerate the practice as a form of precaution (ihtiyat), most ulama assert that it is unnecessary if the first marriage contract was valid. In terms of maslahah mursalah, tajdid nikah can be viewed as beneficial when it reduces stigma and promotes harmony but may be harmful if it reinforces public misconceptions about Islamic legal norms. Therefore, tajdid nikah should not be institutionalized as a religious obligation, and broader legal education is needed to align community practices with sharia principles and Indonesian legal standards.